2006
DOI: 10.1080/14992020600895170
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of 40 Hz auditory steady-state response (ASSR) and cortical auditory evoked potential (CAEP) thresholds in awake adult subjects

Abstract: Evoked potential thresholds using the 40 Hz auditory steady-state response (ASSR) and cortical auditory evoked potential (CAEP) were recorded at 500 Hz and 4000 Hz test frequencies in 36 subjects with normal acuity, and 30 subjects with sensorineural hearing loss. ASSR threshold sensation levels (SLs) were lower in ears with greater degrees of hearing loss, and for the 500 Hz stimulus. Mean SLs (maximum duration of a single recording: 89 seconds) were as follows at 500 Hz and 4000 Hz respectively: normal heari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 34 publications
6
22
2
1
Order By: Relevance
“…In case of ASSR, the mean difference between ASSR thresholds and pure-tone thresholds amounted to 1.75 dB with a standard deviation of 9.66 dB. These findings agree well with those reported by Aoyagi et al (1993) and Tomlin et al (2006). Aoyagi et al (1993) reported a standard deviation of 40-Hz-ASSR threshold differences ranging between 6 and 8 dB across frequency with a correlation coefficient of 0.96.…”
Section: Accuracy Of Threshold Estimation In Cochlear Hearing Loss Pasupporting
confidence: 93%
“…In case of ASSR, the mean difference between ASSR thresholds and pure-tone thresholds amounted to 1.75 dB with a standard deviation of 9.66 dB. These findings agree well with those reported by Aoyagi et al (1993) and Tomlin et al (2006). Aoyagi et al (1993) reported a standard deviation of 40-Hz-ASSR threshold differences ranging between 6 and 8 dB across frequency with a correlation coefficient of 0.96.…”
Section: Accuracy Of Threshold Estimation In Cochlear Hearing Loss Pasupporting
confidence: 93%
“…It has been reported that a CAEP average consisting of 20-50 epochs, and replicated (Garinis & Cone-Wesson, 2007;Thornton, 2007;Tomlin et al, 2006), should provide an adequate SNR for visual response detection and that averaging an excessive number of epochs can be detrimental to response amplitude (Hyde, 1997;Walter, 1964). By contrast, other studies have suggested that extended averaging should not impair response amplitude (Lightfoot & Kennedy, 2006) as the greatest decrease in amplitude occurs from the fi rst to the second epoch after which amplitude stabilizes (Budd et al, 1998;Henry & Teas, 1968;Woods & Elmasian, 1986).…”
Section: Discussionmentioning
confidence: 97%
“…The N1-P2 is exceptionally sensitive to changes in stimulus intensity level, with its amplitude typically increasing in a linear manner with level (Adler & Adler, 1989;Picton et al, 1970Picton et al, , 1977. Because of this, the N1-P2 response has been suggested as an objective estimate of hearing threshold, with studies showing an accuracy of within 10 dB of behavioural values in most adult cases (Hone et al, 2003;Hyde et al, 1986;Lightfoot & Kennedy, 2006;Prasher et al, 1993;Rickards et al, 1996;Tomlin et al, 2006;Tsui et al, 2002;Yeung & Wong, 2007). Indeed, it has been called ''a measure of choice for most older children and adults'' when objectivity and good frequency specificity of the response is required (Stapells, 2002; for review see Hyde, 1997).…”
Section: Sumariomentioning
confidence: 96%